2021
DOI: 10.3389/fphar.2021.694476
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Analog Exendin-4 Ameliorates Cocaine-Mediated Behavior by Inhibiting Toll-Like Receptor 4 Signaling in Mice

Abstract: Exendin-4 (Ex4), a long-lasting glucagon-like peptide-1 analog, was reported to exert favourable actions on inhibiting cocaine-associated rewarding and reinforcing effects of drug in animal models of addiction. However, the therapeutic potential of different dose of GLP-1 receptor agonist Ex4 in different behavioral paradigms and the underlying pharmacological mechanisms of action are incompletely understood. Herein, we firstly investigated the effects of Ex4 on cocaine-induced condition place preference (CPP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 93 publications
(131 reference statements)
3
8
0
Order By: Relevance
“…Additionally, the significant reinstatement of cocaine-induced CPP is induced after reexposure to a half dose of cocaine (10 mg/kg, i.p.). These results are in line with our previous study showing that 20 and 10 mg/kg were sufficient to produce CPP and reinstatement, respectively ( Zhu et al, 2021 ). Furthermore, this study also suggests that the systemic pretreatment with Ex4 after each extinction session significantly prevents the cocaine-priming reinstatement of the conditioned behavior in the study.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the significant reinstatement of cocaine-induced CPP is induced after reexposure to a half dose of cocaine (10 mg/kg, i.p.). These results are in line with our previous study showing that 20 and 10 mg/kg were sufficient to produce CPP and reinstatement, respectively ( Zhu et al, 2021 ). Furthermore, this study also suggests that the systemic pretreatment with Ex4 after each extinction session significantly prevents the cocaine-priming reinstatement of the conditioned behavior in the study.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with a previous study indicating that memory retention could be disrupted after post-learning manipulations (Grecksch and Matthies, 1980). The expression levels of TLR4 within the hippocampus reactivated by cocaine were clearly inhibited by Ex4, similar to a previous study showing that Ex4 plays an anti-inflammatory role (Ajay et al, 2011;Zhu et al, 2021). Consequently, the GLP-1R agonist Ex4 is capable of modulating cocaine-related CPP memory, enhancing extinction, and weakening the cocaine-primed reinstatement by suppressing TLR4 over-expression within the hippocampus, similar to many studies revealing that extinction in substance abuse can be pharmacologically enhanced (Botreau et al, 2006;Paolone et al, 2009).…”
Section: Potential Mechanisms Of Glp-1r Agonist Ex4's Behavioral Actionssupporting
confidence: 92%
“…Recent literature indicated that GLP-1R agonist Ex4 appears highly promising in attenuating the rewarding and reinforcing effects of cocaine addiction (Hernandez and Schmidt, 2019 ; Zhu et al, 2021 ). For instance, systemic administration of Ex4 is believed to play a substantial role in cocaine dependence (Hernandez et al, 2019 ), such as attenuating cocaine-induced CPP, self-administration, and the cocaine-triggered relapse of drug-seeking in an animal model of cocaine use disorder (Engel and Jerlhag, 2014 ; Hayes and Schmidt, 2016 ; Hernandez et al, 2018 ; Hernandez and Schmidt, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, GLP-1RAs have received widespread attention in recent years due to their neuroprotective (Holst et al, 2011;Zhu et al, 2021) and anti-inflammatory effects (Hattori et al, 2010;Chaudhuri et al, 2012;Lee and Jun 2016). For example, exendin-4 has been reported to be effective in reducing inflammation indices, including TLR2, TLR4, NF-κβ, tumor necrosis factor (TNF)-α, and interleukin (IL)-1β (Chaudhuri et al, 2012;Kozela et al, 2017;Li et al, 2020), which have been heavily implicated in cocaine-related memories (Correia et al, 2020).…”
Section: Neuroimmune Mechanismsmentioning
confidence: 99%